Venous pattern of polymicrogyria detected by susceptibility weighted imaging (SWI). (8th December 2015) - Verma, Rajeev K; Wagner, Franca; Weisstanner, Christian; Strozzi, Susi; Lang, Matthias F
We report a case of a 9-year-old boy presenting with spastic-dystonic movement disorder of the right arm. MRI showed vast unilateral left-sided polymicrogyria (PMG) with perisylvian, temporal, frontal, and parietal location. Corresponding to the distinctly reduced gyration, the focal pattern of cortical veins in susceptibility weighted imaging (SWI) was absent due to missing sulcal depth. In contrast, adjacent regions with sufficient sulcal depth revealed a pattern with numerically increased and finer cortical veins. Therefore, with its atypical venous pattern SWI indicates an abnormal parenchymal anatomy and might be an additional helpful tool for diagnosing PMG.